Model Pengeluaran Pemerintah dan Pertumbuhan Ramah Lingkungan Berdasarkan Konsumsi Energi Ramah Lingkungan di Indonesia - Rizka Fadillah; Muhammad Fauzan Pratama; Toni Toni; Rusiadi Rusiadi; Suhendi Suhendi; Lia Nazliana Nasution (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
This research aims to determine the effect of the government expenditure model and green growth based on green energy consumption in Indonesia which has 4 variables, namely carbon emissions, energy consumption, economic growth and government expenditure. The analytical method used in this research is the Vector Auto Regression (VAR) model with the Impulse Response Function (IRF) test, Forecast Error Varince Decomposition (FEVD), stationarity test, cointegration test, structural lag stability test, and optimal lag length test. . The results of the Vector Autoregression research using lag 1 as the basis show the contribution of each variable to the variable itself and other variables. The results of the Vector Autoregression analysis also show that the past variable (t-1) contributes to the current variable, both the variable itself and other variables. From the results of the analysis, there is a reciprocal relationship between one variable and another variable. Response Function Analysis shows the response of other variables to changes in a variable in the short, medium and long term, and it is known that the stability of the response of all variables is formed within a period of 5 years or the medium term. and long term. Variance Decomposition Analysis shows that there are variables that have the largest contribution to the variable itself in the short, medium and long term, such as CO2, EC, and GOV. Meanwhile, another variable that has the greatest influence on the variable itself in the short, medium and long term is CO2 which is strongly influenced by GOV and GDP.